Relationship between Religious Activities and Spiritual Health with Glycemic Control in Patients with Diabetes - S Heidari; M Raisi; H Ahmari- Tehran; A Khorami- Rad (Iran University of Medical Sciences, 2013)
Background & Aim: Spirituality and religion as human dimensions and because of their role in recovery has been increasingly considered. This study was conducted with the aim of assessing relationship between religious activities and spiritual health with glycemic control in patients with type 2 diabetes.   Material & Methods: In this descriptive- correlational study, 154 hospitalized diabetic patients were recruited by convenience sampling from Kamkar and Shahid-Beheshti hospitals in city of Qom, in 2012. Data collection was done by Paloutzian & Ellison's spiritual well-being and Arcury religious activities questionnaires. Venous blood sample was taken for measurement of glycosylated hemoglobin and fasting blood glucose of patients. Data analysis was done by SPSS-PC (v.18) using descriptive statistics, t-test, Pearson correlation and stepwise linear regression.   Results : Mean score and standard deviation of religious activity and spiritual well-being was 40/81±12/93 ( scores range 20-120) and 90/79±12/88 ( scores range 0-65 ) respectively . Glycosylated hemoglobin of 68/8% of patients was ≥7% and 57/1% of the patients had blood sugar of more than 110 mg/dl. There was no significant difference between spiritual well-being and religious activities' scores of patients with glycosylated hemoglobin≥7% and <7% (p=0/324, p=0/888). There was no correlation between spiritual well-being and religious activities with fasting blood glucose (P=0/128, p=0/422). But being religious (in general) was significantly associated with fasting blood glucose (P<0/05).   Conclusion: In this study, religious activities and spiritual well-being scores was not significantly different between patients with controlled and uncontrolled blood glucose. Doing case- control and longitudinal studies with greater sample size and assessing self- care activities of these patients is recommended.   Received: 1 Jul 2013   Accepted: 13 Sep 2013